Códigos de sustentação da linguagem no cotidiano prisional do Rio Grande do Norte: penitenciária estadual de Parnamirim - Oliveira, Hilderline Camara de (2010)
The quarrel, in this study, tells about the language as social practical in the daily of Parnamirim State Prison that is integrated to the Rio Grande do Norte Penitentiary System - SISPERN, destined for men in fulfilment of penalty privative of freedom, in closed regimen. For the accomplishment of the research, the delimited objectives had been to analyze the language repertoires created in the prisional daily, trying to identify how it´s turned into distinct forms of resistance to the mechanisms of control in penitentiary system; to investigate which are the language repertoires created from the new sociability forms developed among prisoners and identify how the language repertoires are expressed in the daily prisional on relations/exercises of power not-institutionalized. In the methodological aspect, the study is in a qualitative boarding, that has as main instrument the interview. The inquiry was possible by means of using instruments for data collection, like as: the direct comment in the prisional daily duly registered as researcher´s ethnographical procedure, the analysis of interns´ cadastre handbooks and the application of half-structuralized interview, to the subjects of the research. The construction and understanding of the study object had been based on authors who argue on the arrest, as: Foucault, Goffman, Carvalho Filho and, in particular was searched the theorical referencial that approaches the language in a social and cultural perspective: Orlandi, Manfred, Bastos and Candiotto, amongst others. Beyond the normative endorsement of the Brazilian legislation, through the Law of Criminal Execution, of the Criminal Code and the Federal Constitution of the country and the legal apparatus in state scope. Still in the research methodological perspective, after the collection the data had been submitted to an analysis of the speech from Foucalt´s theory and in the Orlandi´s perspective, being also qualitative and quantitative. The results had evidenced that the social and juridical profile of the population in the site inquired is not different of others Brazilian prisons, composed for men, in its majority, with age band between 21 and 30 years old, prisoners for practicing crimes against the patrimony, against life, amongst others, and, in special, criminal recidivists. It evidenced, still, that the daily prisional of PSP is characterized for a sociocultural diversity expressed in the relations of power not institutionalized, that contributes for the formation and division of the groups, each one using a set of language codes/ repertoires sustentation. Therefore, the language, in the daily prisional, is one of the ways to understand the singularity of the sociability relations and as social practicing mediated by relations/exercises of power and antagonistic interests, in which each group aims first of all, their own interests. It represents the complexity of the social relations, in the prisional space, with diverse effects, in function of the situation and the moment. The language in the arrest, beyond the communication function, assumes and represents central element for the sociability human being, contributes for its changings and it´s configured as one of the resistance forms of prisoners against the controling, disciplining and monitoring mechanisms of penitentiary system